Langroud river water quality assessment using NSFWQI qualitative indicators - Parisa Kazemi; Fatemeh Shariati; Abdolkarim Keshavarz Shokri (علوم محیطی)
Introduction: There are numerous indices used to determine water quality, among which the National Sanitation Foundation (NSF) index is one of the most functional ones. The aim of the present study was to evaluate the water quality of Langroud River using NSF Water Quality Index (NSFWQI), where 10 parameters including water temperature, turbidity, phosphates, nitrates, dissolved oxygen (DO), fecal coliform, biochemical oxygen demand (BOD), pH, total dissolved solids (TDS), and electrical conductivity (EC) were measured. Material and methods: Seven stations were selected along the river and samples were obtained during four seasons from February 2015 to July 2015. DO, pH, turbidity, and TDS were measured by a portable device. Nitrate and phosphate were determined by spectrophotometry. The temperature was measured by a thermometer. The coliform measurement was done by the 9-tube standard method. Results and discussion: Our results showed that turbidity, temperature, nitrate, phosphate, TDS, pH, and EC had the highest amount in summer, BOD reached its highest value in the spring, the amount of fecal coliform was almost the same in all seasons, and DO had its highest amount in winter. Comparison of the values of NSFWQI at seven stations of Langroud River in different seasons showed that the second station (Darvishanbar, upstream) had the highest value (63) in the winter, and Khalkyaser station (downstream) had the lowest value (56) in the summer. Conclusion: Generally, the results showed that in all stations, the numerical values of indexes are reduced gradually from winter to summer. Interpretation of the results based on NSFWQI indicates that in Langroud River from the first station to the last one, the pollution load increased and the water quality decreased. So, the river’s water is not suitable for drinking and it should be treated before application.